Prevalensi penyakit hipertensi pada masa pandemi COVID-19 di praktik dokter keluarga - Bradley Miracle Kent Korompis; Iyone Esra Tiurma Siagian; Zwingly Christian Jefferson Gerard Porajow (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2022)
Hypertension is one of the leading causes of premature death worldwide. The 2018 Indonesian prevalence of hypertension based on the results of population measurements at the age of 18 years or above was 34.1%. The hypertension prevalence in the North Sulawesi Province is still very high. Health services usually initiate from primary health care, such as primary health centres or family physicians. Family physicians are responsible for providing comprehensive health services to every individual, including hypertension. This study aimed to measure the prevalence of hypertensive patients during the COVID-19 pandemic in family physician practices. This research was a retrospective descriptive study with a cross-sectional study design, starting from October to December 2022. This study used secondary data on patient medical records at family physician practice during the COVID-19 pandemic from June 2021 to May 2022. There were 768 patients in this study. The prevalence of hypertension patients in family practice during the COVID-19 pandemic was 31.3%. The majority of patients were above 65 years old and female groups. Keywords: hypertension, prevalence, distribution